Advancing research for HIV prevention among African, Caribbean and Black men: Protocol for a multisite cross-sectional study in Ontario (weSpeak study). Issue 18 (7th May 2021) - Husbands, Winston; Etowa, Josephine; Oakes, Wesley; Omorodion, Francisca; Luginaah, Isaac; Etowa, Egbe; Ghose, Bishwajit; Wong, Josephine Pui-Hing
Abstract : Abstract: In Ontario, African, Caribbean, and Black (ACB) men account for almost 60% of the estimated number of HIV-positive people (through heterosexual contact), although they constitute less than 5% of the province's population. However, current HIV research, programming and policy in Ontario are not aligned with heterosexual ACB men's healthcare needs and interests, and fail to engage them in community responses to HIV. weSpeak is a multisite (Ottawa, Toronto, London, and Windsor) project that is aims to: assess the sociocultural and socio-political conditions that contribute to HIV related health disparities among ACB men, examine social and behavioral vulnerabilities to HIV among ACB men, including their social identities related to race, class, gender and sexualities, community engagement and mobilization part of the project, and generate, appraise and share new knowledge, and support its translation into intervention and practice. This will be a mixed method study comprising focus groups, in-depth interviews, and a survey to meet the data objectives. All data collection activities will take place at the same time in 4 cities in 3 sequential phases: focus groups, in-depth interviews, and a questionnaire survey. Service providers will participate in the concept mapping exercise to review the research findings and develop program, policy, and community-based initiatives to promote resilience and meaningfully engage heterosexual ACB men in community responses to HIV survey. This study will provide evidence on: heterosexual ACB men's experience of structural disadvantage and psychological factors is associated with HIV vulnerability. heterosexual ACB men with greater internal resilience and social resources show greater risky behaviors, and a conceptual Model of HIV vulnerability linking the potential internal and external factors that interact to influence HIV vulnerability. This study will lead to better understanding of the structural determinants and the psychosocial risk factors of HIV transmission among ACB men in Ontario which will aid in designing evidence-based intervention programs, and thereby reduce their higher vulnerability to HIV and its associated consequences.